An interlaboratory comparison exercise for the determination of microplastics in standard sample bottles. (September 2019) - Isobe, Atsuhiko; Buenaventura, Nina T.; Chastain, Stephen; Chavanich, Suchana; Cózar, Andrés; DeLorenzo, Marie; Hagmann, Pascal; Hinata, Hirofumi; Kozlovskii, Nikolai; Lusher, Amy L.; Martí, Elisa; Michida, Yutaka; et al.
Abstract: An interlaboratory comparison exercise was conducted to assess the consistency of microplastic quantification across several laboratories. The test samples were prepared by mixing one liter seawater free of plastics, microplastics made from polypropylene, high- and low-density polyethylene, and artificial particles in two plastic bottles, and analyzed concurrently in 12 experienced laboratories around the world. The minimum requirements to quantify microplastics were examined by comparing actual numbers of microplastics in these sample bottles with numbers measured in each laboratory. The uncertainty was due to pervasive errors derived from inaccuracies in measuring sizes and/or misidentification of microplastics, including both false recognition and overlooking. The size distribution of microplastics should be smoothed using a running mean with a length of >0.5 mm to reduce uncertainty to less than ±20%. The number of microplastics <1 mm was underestimated by 20% even when using the best practice for measuring microplastics in laboratories. Highlights: An interlaboratory comparison exercise was conducted across 12 laboratories. Samples were prepared by mixing seawater, man-made microplastics, and particles. The minimum requirements to quantify microplastics were examined. The number of microplastics <1 mm was underestimated by 20%.